Mathematical Model of Fluid Flow Machine Unit for a Small-Scale Compressed Gas Energy Storage System - Piotr Lis; Jarosław Milewski; Pavel Shuhayeu; Jan Paczucha; Paweł Ryś (Energies)
This study presents a comprehensive dynamic model of a small-scale, solar-powered hydraulic gas compression energy storage system tailored for renewable energy applications. Addressing the intermittency of renewable energy sources, the model incorporates mass, momentum, and energy conservation principles and is implemented using GT-Suite simulation software v2025.0. The system, based on a liquid piston mechanism, was analyzed under both adiabatic and isothermal compression scenarios. Validation against experimental data showed maximum deviations under 10% for pressure and 5 °C for temperature. Under ideal isothermal conditions, the system stored up to 8 MJ and recovered 6.1 MJ of energy, achieving a round-trip efficiency of 76.3%. In contrast, adiabatic operation yielded 52.6% efficiency due to thermal losses. Sensitivity analyses revealed the importance of heat transfer enhancement, with performance varying by over 15% depending on spray cooling intensity. These findings underscore the potential of thermally integrated hydraulic systems for efficient, scalable, and cost-effective energy storage in distributed renewable energy networks.